A Comparative Study on Absorption of Gaseous Formaldehyde by Electrospun Biomass Carbon Nanofiber Membranes Modified by Plasma Activation and Chemical Treatment - Qian He; Jinhui Xiong; Huanbo Wang; Linkun Xie; Xijuan Chai; Lianpeng Zhang; Siqun Wang; Guanben Du; Kaimeng Xu (Molecules)
To comparatively study the effects of cold plasma activation and chemical treatment on the adsorption capacities of biomass carbon nanofiber membranes (BCNMs), microcrystalline cellulose (MCC) and chitosan (CS) were used to fabricate porous BCNMs by electrospinning and carbonization. Two modification methods, including oxygen (O2) plasma activation and chemical treatment using nitric acid (HNO3), sulfuric acid (H2SO4), hydrogen peroxide (H2O2), and urea, were further employed to enhance their adsorption performance. Various carbonyl group (C=O), ether bond (C-O), carboxyl group (O-C=O) and pyridinic nitrogen (N), pyrrolic N, and quaternary N functional groups were successfully introduced onto the surface of the BCNMs by the two methods. The BCNM-O2 showed optimal formaldehyde absorption capacity (120.67 mg g−1), corresponding to its highest contents of N, O-containing functional groups, and intact network structure. However, chemical treatment in strong acid or oxidative solutions destructed the microporous structures and changed the size uniformity of fibers in the BCNMs, resulting in a decline in formaldehyde adsorption capacity. A synergistically physical–chemical adsorption took place during formaldehyde adsorption by the modified biomass nanofiber membranes, due to the coexistence of suitable functional groups and porous structures in the membranes.